Auto Tuning PID Kontrol Pada Inkubator Bayi - Pradipta Rezkyasa, I Putu Pasek; Adhi Suryawan, A.A.; Nitya Santhiarsa, I Gusti Ngurah (Teknik Desain Mekanika; Vol 10 No 2 (2021): April 2021 : Teknik Desain Mekanika, 2021)
Abstract Lack of fatty tissue under the skin is one of the factors in premature babies experiencing hypothermia or low body temperature. In addition, baby incubators are also useful so that premature babies are protected from direct contact with the surrounding environment because the function of the organs in premature babies is not yet perfect. To make a baby incubator in ideal conditions for premature babies, it requires a temperature of 33 to 35 degrees Celsius and a relative humidity of about 40% to 60% to help premature babies maintain their body temperature. Therefore, we need an automatic control system that can control the temperature and humidity in the infant incubator so that the handling of premature babies can be improved and reduce the negligence factor of medical personnel. An Arduino Mega 2560 microcontroller, Arduino Uno, LM35 sensor, DHT22 sensor is required to control the temperature and humidity in the baby incubator. The results obtained from the research on the prototype of a baby incubator without load and with a load of 2 kg reached a stable temperature of 34 danC and humidity of 40% to 60% RH in the infant incubator. Using the Auto Tuning PID control method on the no-load test, the maximum overshoot value (Mp) = 4.9111%, the average error signal = 3.8666% and reaches a steady state at 1023 seconds. In the test with a load of 2 kg, the maximum overshoot value (Mp) was obtained = 3.6317%, the average error signal = 2.3696% and reached a steady state at 5924 seconds. Keywords: Arduino Mega 2560; Arduino Uno; LM35 Sensor; DHT22 Sensor